Breathing exercise dan penggunaan masker sebagai terapi dalam meningkatkan kapasitas vital paru pada pekerja - Trisna Dewita; Rizqi Ulla Amaliah; M.Kafit (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: High levels of dust in the air can affect lung function, to prevent the occurrence of diseases of the lungs caused by dust exposure, it is necessary to use a mask at work and in an effort to increase the lung's vital capacity due to exposure to dust at work can be done with breathing exercises (Breathing) Exercise) and is expected to improve lung ventilation function.Objective: The purpose of this study was to study the interaction of the application of breathing exercises and the use of masks to increase lung capacity.Methods: This research is a quasy experiment research with a complete random design in two directions. The treatments were tested in four groups namely, breathing exercise, the use of mask, breathing exercise and the use of masks and control groups.Results: The average vital lung capacity in the treatment group with the interaction of the use of masks and the application of breathing exercise is 4.3 L, in the group using the 3.0 L mask, in the group that does breathing exercise 3.1 L while in the control group that does not use masks and applying breathing exercises with an average capacity of 2.7L.Conclusion: Breathing exercises and the use of a mask for 1 month continuously can increase the vital capacity of the lungs.